Persistent alterations of gene expression profiling of human peripheral blood mononuclear cells from smokers. Issue 10 (21st August 2015) - Weng, Daniel Y.; Chen, Jinguo; Taslim, Cenny; Hsu, Ping‐Ching; Marian, Catalin; David, Sean P.; Loffredo, Christopher A.; Shields, Peter G.
Abstract : The number of validated biomarkers of tobacco smoke exposure is limited, and none exist for tobacco‐related cancer. Additional biomarkers for smoke, effects on cellular systems in vivo are needed to improve early detection of lung cancer, and to assist the Food and Drug Administration in regulating exposures to tobacco products. We assessed the effects of smoking on the gene expression using human cell cultures and blood from a cross‐sectional study. We profiled global transcriptional changes in cultured smokers' peripheral blood mononuclear cells (PBMCs) treated with cigarette smoke condensate (CSC) in vitro ( n = 7) and from well‐characterized smokers' blood ( n = 36). ANOVA with adjustment for covariates and Pearson correlation were used for statistical analysis in this study. CSC in vitro altered the expression of 1 178 genes (177 genes with> 1.5‐fold‐change) at P < 0.05. In vivo, PBMCs of heavy and light smokers differed for 614 genes (29 with> 1.5‐fold‐change) at P < 0.05 (309 remaining significant after adjustment for age, race, and gender). Forty‐one genes were persistently altered both in vitro and in vivo, 22 having the same expression pattern reported for non‐small cell lung cancer. Our data provides evidence that persistent alterations of gene expression in vitro and in vivo may relate to carcinogenic effects of cigarette smoke, and the identified genes may serve as potential biomarkers for cancer. The use of an in vitro model to corroborate results from human studies provides a novel way to understand human exposure and effect. © 2015 Wiley Periodicals, Inc.